Alternative technologies of manufacture and decoration of wood balusters; IOP Conference Series: Materials Science and Engineering; Vol. 66: 20th International Conference for Students and Young Scientists: Modern Techniques and Technologies (MTT'2014), Tomsk, Russia, 14-18 April 2014 - Krauinsh D. P. Dmitry Petrovich; Zhukova N. S. Nina Stepanovna; Volkova M. G. Marina Gennadevna; Kukhta A. (2014, 2014)
Title screen